School management: The optimization of learning facilities to improve the quality of vocational schools - Rahman Setia; Dindin Nasrudin (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
The creation of qualified graduates is a parameter of the implementation of quality education. Vocational schools become one of the learning places to produce quality human resources who are ready to enter the world of business and industry. Effective and efficient management of learning facilities and infrastructure is a leadership strategy of the school's related parties to improve the quality of graduates. This research uses a qualitative approach with a case-study design. A total of three vocational schools in Sumedang Regency were selected as research sites. This research aims to understand, describe, and analyze the school principals' leadership strategies in managing and developing learning facilities and infrastructure to improve their graduates' quality. The research data were collected through observation, interviews, documentation studies, and field notes. The results show that despite all the problems due to the limited availability of practical equipment and the minimal cost allocated, vocational schools in Sumedang Regency can produce graduates with the industrial world's certified expertise competencies. The use of learning facilities and infrastructure to improve graduates' quality in the three vocational schools participating in the research has been running optimally. However, the strategy for developing learning facilities and infrastructure has not been implemented as expected. Planning, implementation, and supervision are stages that must be highly considered by school principals in managing learning facilities and infrastructure.